2013
DOI: 10.1038/ncb2799
|View full text |Cite
|
Sign up to set email alerts
|

A soft cortex is essential for asymmetric spindle positioning in mouse oocytes

Abstract: At mitosis onset, cortical tension increases and cells round up, ensuring correct spindle morphogenesis and orientation. Thus, cortical tension sets up the geometric requirements of cell division. On the contrary, cortical tension decreases during meiotic divisions in mouse oocytes, a puzzling observation because oocytes are round cells, stable in shape, that actively position their spindles. We investigated the pathway leading to reduction in cortical tension and its significance for spindle positioning. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
220
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(240 citation statements)
references
References 59 publications
12
220
1
7
Order By: Relevance
“…One of the hallmarks of this step is the assembly of the mitotic spindle. Contractility affects spindle architecture function and orientation and, therefore, can affect the fate of the daughter cell (Carreno et al, 2008;Chaigne et al, 2013;Kunda et al, 2008;Thery et al, 2005). The separation of the two cells takes place during cytokinesis; it relies on the cleavage furrow contractile zone, a structure in which actomyosin-derived forces play a major role (Mendes Pinto et al, 2013;Pollard, 2010).…”
Section: Cellular Functions Of the Contractomementioning
confidence: 99%
“…One of the hallmarks of this step is the assembly of the mitotic spindle. Contractility affects spindle architecture function and orientation and, therefore, can affect the fate of the daughter cell (Carreno et al, 2008;Chaigne et al, 2013;Kunda et al, 2008;Thery et al, 2005). The separation of the two cells takes place during cytokinesis; it relies on the cleavage furrow contractile zone, a structure in which actomyosin-derived forces play a major role (Mendes Pinto et al, 2013;Pollard, 2010).…”
Section: Cellular Functions Of the Contractomementioning
confidence: 99%
“…However during the last years, the development of new actin probes that bind to F-actin rather than Gactin, such as Lifeact or GFP-UtrCh revealed other pools of Factin in the cytoplasm or around the spindle in mitotic cells [46]. Recently, the use of this probe coupled with live imaging and biophysical approach resulted in new relevant discoveries [47]. In particular, this research revealed new levels of complexity in the dynamic and regulation of F-actin during meiotic maturation of mouse oocytes and linked the thickening of the cortical F-actin (composed by two distinct outer and inner layers) to an increase in cortical plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Ce réseau dépend de la formine-2, un nucléateur cellulaires ; en particulier ces protéines sont responsables de l'augmentation de la tension corticale dans la plupart des cellules mitotiques. Dans les ovocytes, la myosine-II est enrichie au cortex des ovocytes en prophase contribuant ainsi à une tension élevée, puis elle est progressivement exclue du cortex, ce qui est reflété par la chute de tension corticale dans les stades tardifs de la méiose I. Cet évènement est également contrôlé par la voie mos/MAPK [11] ; ainsi dans les ovocytes mos-/-dépour-vus d'épaississement cortical, la myosine-II est toujours enrichie au cortex en méiose I, ce qui corrèle avec le maintien d'une tension corticale élevée. En outre, l'épaississement du cortex d'actine contribue également à ramollir le cortex en augmentant sa plasticité, c'est-à-dire sa capacité à être déformé et à conserver la déformation ( Figure 2B).…”
unclassified
“…En outre, l'épaississement du cortex d'actine contribue également à ramollir le cortex en augmentant sa plasticité, c'est-à-dire sa capacité à être déformé et à conserver la déformation ( Figure 2B). Ce ramollissement est indispensable à la migration du fuseau puisque durcir le cortex artificiellement l'empêche [11]. Comment expliquer que ramollir le cortex soit indispensable à la migration du fuseau ?…”
unclassified
See 1 more Smart Citation